Using ODP Boreholes for Studying Sub-seafloor Hydrogeology: Results from the First Decade of CORK Observations - Davis, Earl; Becker, Keir (Geoscience Canada, 2001)
Summary A system for sealing and instrumenting ODP boreholes was developed 10 years ago to allow interstitial fluids to be sampled, and natural fluid pressures and temperatures to be monitored over long periods of time. The capabilities of these CORK (Circulation Obviation Retrofit Kit) observatories have been expanded recently to allow monitoring and sampling in multiple isolated horizons, and to allow installations to be completed by wirelinein previously drilled holes. To date, 16 hydrologie observatory sites have been established in ridge crest, ridge flank, and accretionary prism settings. Observations at these sites have provided precise constraints on the primary driving forces for, and thermal consequences of, sub-seafloor fluid flow caused by tectonic consolidation and thermal buoyancy. Deep in accretionary prisms, high formation pressures have been observed, confirming that plate boundary faults possess little strength. In young ocean crustai settings, surprisingly low lateral temperature and pressure gradients have been documented, implying that the extrusive rocks of the oceanic crust permit efficient fluid, heat,and chemical transport over distances of many kilometres. CORK observations have also revealed pressure variations and associated fluid flow resulting from coseismic plate deformation, and from tidal, océanographie, and barometric loading ofthe seafloor. The characteristics of the formation response to seafloor loading provide constraints on elastic and hydrologic properties, and allow quantitative estimates of crustai strain to be made from tectonic-strain-related pressure transients. Strain events have been observed up to150 km away from several seismogenic dislocations along transform and seafloor spreading plate boundaries.